The Analysis of Code Switching Used by Maudy Ayunda in “Catatan Najwa” Youtube Channel (Undergraduate Conference on Applied Linguistics, Linguistics, and Literature, 2022)
A good technique to communicate with others and build communication is through language. We use language to explore ideas, views, knowledge, and feelings about an event by understanding what is said or what other people think. Bilinguals are those who are fluent in two languages both orally and in writing. The purpose of this study was to identify the types of code switching and the contexts in which Maudy Ayunda used them. Sociolinguistics includes the study of code switching. Language analysis is studied in sociolinguistics. The linguistic component is connected to elements outside of the language, such as how speakers, particularly the speech community, utilize language. Code switching usually occurs while talking to someone. The source of the research is the talk show Catatan Najwa with Maudy Ayunda on Najwa Shihab's Youtube Channel. In this talk show, there was a guest star named Maudy Ayunda. She recently graduated from Oxford University and spoke with Najwa Shihab. The conversation took place on Najwa Shibah's Youtube Channel. In this conversation, they use two languages, namely Indonesian and English. This study used descriptive qualitative method. To complete the data, the researchers also conducted a literature study. This research is focused on Najwa Shihab's Youtube video channel. The results of the research is Intra-Sentential with 15 data as dominant code switching types and Have Strong Opinions about Something with 9 data as dominant code switching contexts.
Keywords: bilingualism, sociolinguistic, code-switching